The New Testament Moses in the Context of Ancient Judaism - Lierman, John D. (Tyndale bulletin, 2002)
A dissertation assessing how the New Testament, set within the context of ancient Judaism, characterizes the functions of Moses in relation to Israel and the Jewish people.